Grappling with the Multifaceted World of the DNA Damage Response - Antonio Porro (Frontiers Research Topics, 2017)
DNA damage is a major threat to genomic integrity and cell survival. It can arise both spontaneously and in response to exogenous agents. DNA damage can attack most parts of the DNA structure, ranging from minor and major chemical modifications, to single-strand breaks (SSBs) and gaps, to full double-strand breaks (DSBs). If DNA injuries are mis-repaired or unrepaired, they may ultimately result in mutations or wider-scale genome aberrations that threaten cell homeostasis. Consequently, the cells elicit an elaborate signalling network, known as DNA damage response (DDR), to detect and repair these cytotoxic lesions. This Research Topic was aimed at comprehensive investigations of basic and novel mechanisms that underlie the DNA damage response in eukaryotes.DNA damage is a major threat to genomic integrity and cell survival. It can arise both spontaneously and in response to exogenous agents. DNA damage can attack most parts of the DNA structure, ranging from minor and major chemical modifications, to single-strand breaks (SSBs) and gaps, to full double-strand breaks (DSBs). If DNA injuries are mis-repaired or unrepaired, they may ultimately result in mutations or wider-scale genome aberrations that threaten cell homeostasis. Consequently, the cells elicit an elaborate signalling network, known as DNA damage response (DDR), to detect and repair these cytotoxic lesions. This Research Topic was aimed at comprehensive investigations of basic and novel mechanisms that underlie the DNA damage response in eukaryotes.